Sintesis dan Karakterisasi Nanopartikel Tembaga dengan Bioreduktor Limbah Kulit Buah Naga (Hylocereus costaricensis) - Qomariyah, Ani; Istatik Badi'ah, Hanim (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2024)
The green chemistry technique was carried out for the very first time to synthesize copper nanoparticles (Cu-NPs) by applying CuSO4 as a precursor and red dragon fruit peel extract as a reducing agent. The extracting procedure of red dragon fruit peel was conducted by maceration technique with solvent of methanol. Cu-NPs were produced through green chemistry by the reduction method. Cu-NPs were prepared by combining CuSO4 solution with red dragon fruit peel extract in the compositions of 1:1, 1:2, 1:3, 1:4, and 1:5. The successfully synthesized Cu-NPs were analyzed using Scanning Electron Microscopy (SEM), Particle Size Analyzer (PSA), and UV-Visible Spectrophotometer. The variation in the volume of reducing agent affect the maximum wavelength produced. The optimum concentration of reducing agent (1:5) shows the highest intensity at 650 nm. The optimum pH for the synthesis of copper nanoparticles (Cu-NPs) with dragon fruit extract was 6. Cu-NPs were stable at 20 minutes to 1 hour. From the SEM figure of Cu-NPs, it can be observed that the particles are of round shape. Volume or weight analyzes of Cu-NPs employing PSA provided particle diameters between 80 and 120 nm with an approximate distribution of 100 nm.